The Role of Spatial Political Economy in Shaping Urban Design - Mojtaba Lorzangeneh (Dimensi: Journal of Architecture and Built Environment)
Like other disciplines, urban design is grounded in substantial theoretical foundations, despite differences among experts. Although urban design has undergone significant transformations over time, the evolving needs of urban spaces have played a critical role in shaping its adaptation. Notably, the theoretical and real objects of urban design—civil society and the public realm—are regarded as superior to those of related fields such as architecture and civil engineering. The development of a robust theoretical foundation for urban design through the lens of spatial political economy, as conceptualized by Alexander Cuthbert, has proven to be highly valuable. Cuthbert identified the integrative knowledge of urban design as the outcome of a coherent foundation that unites both theory and practice. This research adopts a theoretical and fundamental approach, utilizing a descriptive-analytical method and employing content analysis. By examining the evolution of Cuthbert's perspectives, the study seeks to analyze urban design through the framework of spatial political economy. The findings indicate that the dialectical relationship between urban design and Spatial Political Economy (SPE) establishes urban design as a distinct and structured discipline. This mutual dialectic is reflected in the process of place-making, where the production and reproduction of space align with the principles of SPE, and urban design serves as the mechanism for shaping urban spaces. It is clear that urban design stands as its own discipline, without requiring idealizations borrowed from other fields. Spatial Political Economy provides the most comprehensive framework for understanding urban design. Cuthbert’s perspective ultimately fosters a convergence of overlapping ideas, enabling the development of a strong theoretical foundation for urban design that promotes the enhancement of the public realm in cities.